Pengembangan LKPD Berbasis ICARE (Introduction, Connect, Apply, Reflect, Extend) pada Materi Penentuan Perubahan Entalpi Untuk SMA/MA - Endah Tri Handayani (UIR Press, 2021)
This Research aims to develop Student Activity Worksheet (LKPD) based on ICARE of determination of the enthalpy changes subject for class XI SMA/MA valid based on content feasibilities, characteristics ICARE, linguistic, presentation, and graphics. The type of this research is development research (Research and Development) with the process referring to the plomp development model. The object of this research is LKPD based on ICARE. Data collection instruments was a validation sheets filled by 3 validators, the results of the validity data analysis of feasibility aspect of content, characteristics of ICARE, language, presentation and graphics are 92,59%, 96,67%, 95%, 97,22%, and 95,83% with valid category. LKPD that has been valid by validators was tested on 20 students and got response results with score 3,45 with very good criteria, and 3 teachers got response result with score 3,6 with very good criteria. From results of analysis data can conclusion that LKPD based on ICARE developed was valid and can be applied for determination of the enthalpy changes subject.